People’s Perception about Plant-based Formulated Diets as a Non-chemical Method of Rodent Population Control in Nigeria (2022)
A total number of two hundred and thirty five (235) respondents responded to the self-structured (online Google form) questionnaires administered to them without being bias to sample their opinions on the performance of common rodent population control methods and their readiness to embrace plant-based formulated diets as a method of rodent population control in Nigeria. Statistical Package for Social Sciences (SPSS) was used to analyze the questionnaires. The results showed that rodent population should be controlled to reduce their damage to agricultural crops (97.4%), to reduce zoonotic diseases (94.9%), and for conservation reasons (82.6%) in Nigeria. It was also revealed that some of the common rodent population control methods were found to be humane, cost effective, acceptable, and effective but at different levels. The plant-based formulated diet as a method of population reduction would be humane (69.8%), acceptable (65.1%), and effective (68.5%) method. The plant-based formulated diet was viewed as a promising method and this indicated readiness to adopt the method as an alternative to the common methods of rodent population control.